Between Tradition And Modernization: Saigo Takamori As The “Last Samurai” Phenomenon - Rustam Mamajonov (Frontline Social Sciences and History Journal, 2026)
This article analyzes the essence and historical assessment of the phenomenon of Saigo Takamori within the framework of the historical contradictions that emerged between tradition and modernization during the Meiji Restoration. The study examines Saigo Takamori’s role in the collapse of the Tokugawa shogunate, his political and military activities in restoring imperial authority, and his position toward the early modernization policies of the Meiji state. Particular attention is given to how Saigo’s views – grounded in samurai ethics, loyalty, and justice – came into conflict with the construction of a centralized, bureaucratic, and Westernized state. The research interprets Saigo not only as a historical figure but also as a socio-political and moral symbol reflecting the internal contradictions of Meiji modernization. The study concludes that the Saigo Takamori phenomenon represents the historical embodiment of traditional values and samurai ideology that were marginalized during Japan’s transition to a modern state. This perspective allows for a deeper understanding of the nature of Meiji reforms.